Regulation of communication in Portugal and social movements: a study on the relationship between the media and the activism - Trindade, Ana Carolina [UNESP]; Luvizotto, Caroline Kraus [UNESP] (Univ Rey Juan Carlos, Fac Ciencias Juridicas & Sociales, 2022)
The mass media or media here are treated as synonyms, and they have an important role in the construction of public opinion since they can attribute visibility to the facts and describe them at their discretion. This article aims to reflect on the performance of social movements and their relationship with the media in Portugal, seeking to identify the mechanisms of participation and visibility provided to activists by the Portuguese media system. The methodology used is composed of documentary and bibliographic research, as well as qualitative research carried out by a focus group of activists and Portuguese citizens carried out in the city of Lisbon in February 2020, tidy ascertain their experiences and perceptions of the media system. The results of the focus group suggest that despite the existence of media regulation in Portugal, the media do not provide support or space for activists, harming the visibility and public opinion about portuguese social movements. Thus, it is concluded that the absence of a media space for activists and social movements results in the alternative of inserting demands, agendas and mobilizations of citizens into digital social networks.
Keywords: activism; mass media; social movements; Portugal; regulation of communication